Insulin-Activated Protein Kinase Cβ Bypasses Ras and Stimulates Mitogen-Activated Protein Kinase Activity and Cell Proliferation in Muscle Cells - Formisano, Pietro (American Society for Microbiology, 2000)
In L6 muscle cells expressing wild-type human insulin receptors (L6hIR), insulin induced protein kinase Cα (PKCα) and β activities. The expression of kinase-deficient IR mutants abolished insulin stimulation of these PKC isoforms, indicating that receptor kinase is necessary for PKC activation by insulin. In L6hIR cells, inhibition of insulin receptor substrate 1 (IRS-1) expression caused a 90% decrease in insulin-induced PKCα and -β activation and blocked insulin stimulation of mitogen-activated protein kinase (MAPK) and DNA synthesis. Blocking PKCβ with either antisense oligonucleotide or the specific inhibitor LY379196 decreased the effects of insulin on MAPK activity and DNA synthesis by >80% but did not affect epidermal growth factor (EGF)- and serum-stimulated mitogenesis. In contrast, blocking c-Ras with lovastatin or the use of the L61,S186 dominant negative Ras mutant inhibited insulin-stimulated MAPK activity and DNA synthesis by only about 30% but completely blocked the effect of EGF. PKCβ block did not affect Ras activity but almost completely inhibited insulin-induced Raf kinase activation and coprecipitation with PKCβ. Finally, blocking PKCα expression by antisense oligonucleotide constitutively increased MAPK activity and DNA synthesis, with little effect on their insulin sensitivity. We make the following conclusions. (i) The tyrosine kinase activity of the IR is necessary for insulin activation of PKCα and -β. (ii) IRS-1 phosphorylation is necessary for insulin activation of these PKCs in the L6 cells. (iii) In these cells, PKCβ plays a unique Ras-independent role in mediating insulin but not EGF or other growth factor mitogenic signals.